2020
DOI: 10.14245/ns.2040250.125
|View full text |Cite
|
Sign up to set email alerts
|

Transforaminal Endoscopic Thoracic Discectomy: Technical Review to Prevent Complications

Abstract: For all the spine surgeons, thoracic disc herniations (TDHs) entrust a real challenge in terms of patient diagnosis, proper selection, surgical technique, and potential adverse events. TDHs are relatively uncommon compared to the lumbar and cervical levels. Literature reports a variable prevalence of TDHs around 6% to 40%, but less than 1% of all disk herniations are symptomatic TDHs, evidencing as a relatively unusual condition. Nowadays, transforaminal endoscopic thoracic discectomy (TETD) has been implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 29 publications
0
14
0
1
Order By: Relevance
“…Heat injury from use of laser or radiofrequency might be a concern for the surgeon due to the anatomy of the thoracic canal, with a higher density of the spinal cord compared to the multiple roots in the lumbar region. 68 Although there is less CSF to buffer against heat, full endoscopy is performed under continuous irrigation mitigating this risk. It is interesting to note that, with respect to the open approaches, the lateral and posterolateral approaches had lower overall complications than the anterior approaches (although the latter were reduced with thoracoscopy), but were more liable to inadequate decompression.…”
Section: Discussionmentioning
confidence: 99%
“…Heat injury from use of laser or radiofrequency might be a concern for the surgeon due to the anatomy of the thoracic canal, with a higher density of the spinal cord compared to the multiple roots in the lumbar region. 68 Although there is less CSF to buffer against heat, full endoscopy is performed under continuous irrigation mitigating this risk. It is interesting to note that, with respect to the open approaches, the lateral and posterolateral approaches had lower overall complications than the anterior approaches (although the latter were reduced with thoracoscopy), but were more liable to inadequate decompression.…”
Section: Discussionmentioning
confidence: 99%
“…Paramedian soft herniation with pain is the best indication for them. With experienced hands, challenging cases like myelopathy or calcified disc can be safely performed [ 1 , 2 , 11 13 ]. Concomitant ossification of the posterior longitudinal ligament or spinal infection is excluded.…”
Section: Methodsmentioning
confidence: 99%
“…The basic concept for the transforaminal or interlaminar approach is similar to the lumbar spine [ 8 10 ]. Endoscopic approaches to the thoracic spine have been reported and found to be safe and effective as well as avoiding approach-related complications with injury to the visceral and vascular structure [ 1 , 2 , 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…(3) Thoracic FESS Most authors have reported good outcomes on their FESS approaches in the thoracic spine. In one of the largest series reported by Bae et al on 92 patients undergoing full endoscopic surgery of the thoracic spine, they reported excellent or good outcomes(Modified Macnab's criteria) in 90% patients 159) . Complications were reported in 6.5% patients out of which 2 had recurrent disc herniation.…”
Section: )mentioning
confidence: 97%
“…It is worthwhile to note that these extended indications once formed contraindications to endoscopy. Generally, patients with profound neurological deficits due to significant myelopathy, history of previous spine surgery and multi-level involvement are few contraindications for this type of surgery 159) . TETD though has been recently contraindicated in patients with severe acute or progressive myelopathy due to hard or calcified disc herniation, OPLL and severe disk narrowing, Costotransverse joint needs to be drilled to widen the access in most of the cases 160) .…”
Section: )mentioning
confidence: 99%